Research methods for sports performance analysis - O'Donoghue, P. (Routledge, 2010)
Modern techniques of sports performance analysis enable the sport scientist, coach and athlete to objectively assess, and therefore improve upon, sporting performance. They are an important tool for any serious practitioner in sport and, as a result, performance analysis has become a key component of degree programmes in sport science and sports coaching.